Complications associated with the use of resuscitative endovascular balloon occlusion of the aorta (REBOA): an updated review - Megan Brenner; Marcelo Augusto Fontenelle Ribeiro Junior; Salman M Salman; Sally M Al-Qaraghuli; Farah Makki; Riham A Abu Affan; Shahin Reza Mohseni (Trauma Surgery & Acute Care Open)
Resuscitative endovascular balloon occlusion of the aorta (REBOA) has become part of the arsenal to temporize patients in shock from severe hemorrhage. REBOA is used in trauma to prevent cardiovascular collapse by preserving heart and brain perfusion and minimizing distal hemorrhage until definitive hemorrhage control can be achieved. Significant side effects, including death, ischemia and reperfusion injuries, severe renal and lung damage, limb ischemia and amputations have all been reported. The aim of this article is to provide an update on complications related to REBOA. REBOA has emerged as a critical intervention for managing severe hemorrhagic shock, aiming to temporize patients and prevent cardiovascular collapse until definitive hemorrhage control can be achieved. However, this life-saving procedure is not without its challenges, with significant reported side effects. This review provides an updated overview of complications associated with REBOA. The most prevalent procedure-related complication is distal embolization and lower limb ischemia, with an incidence of 16% (range: 4–52.6%). Vascular and access site complications are also noteworthy, documented in studies with incidence rates varying from 1.2% to 11.1%. Conversely, bleeding-related complications exhibit lower documentation, with incidence rates ranging from 1.4% to 28.6%. Pseudoaneurysms are less likely, with rates ranging from 2% to 14%. A notable incidence of complications arises from lower limb compartment syndrome and lower limb amputation associated with the REBOA procedure. Systemic complications include acute kidney failure, consistently reported across various studies, with incidence rates ranging from 5.6% to 46%, representing one of the most frequently documented systemic complications. Infection and sepsis are also described, with rates ranging from 2% to 36%. Pulmonary-related complications, including acute respiratory distress syndrome and multisystem organ failure, occur in this population at rates ranging from 7.1% to 17.5%. This comprehensive overview underscores the diverse spectrum of complications associated with REBOA.